Analysis of the Dynamics of Foreign Currency Exchange Rates in Ukraine Including Seasonality Factors and Demand for Domestic Government Loans Bonds (Over 5-10 Years) - Violetta Roshylo; Samuel Long (Науковий вісник Мукачівського державного університету. Серія Економіка, 2021)
The relevance of the scientific article lies in the need to substantiate the importance of the role of currency exchange rates for the robust functioning of the country’s economy. The purpose of the article is to analyse the dynamics of foreign currency exchange rates, mainly the dollar, and the euro, in Ukraine, taking into account factors of seasonality and demand for government bonds. The main methods used in the paper are statistical empirical research methods, in particular modelling. It was determined that the export of raw materials, mainly steel, and various agricultural crops such as wheat, corn, sunflower oil, soybeans, etc., plays a particularly important role in Ukraine. It was found out that the mentioned fluctuations in export are one of the reasons for the currency seasonality, but not the only one or the main reason, as the exchange rate is strongly influenced by oil, gas, and other energy resources prices, which the country needs constantly, especially during the heating season. The exchange rate of the hryvnia over the last five years within the context of the National Bank of Ukraine has also been analysed. It was found that the demand for government loans bonds is one of the most important factors in considering the foreign currencies exchange rates in Ukraine. To make models more plausible and to reduce the influence of other factors in determining seasonality of the currency with certain currency pairs with the dollar, euro, yen, zloty, and ruble, the data for the last several years has been used, which are less likely to be distorted by the influence of external factors. It has been confirmed that a successful trade policy is a key source of currency stabilisation in Ukraine. The article is useful for studying the functioning of currencies in general; for studying the economy of Ukraine, especially the country’s currency issues; for students of various economic disciplines